Reaction-induced swelling of ionic gels. Issue 3 (20th November 2014) - Liu, ShaoBao; Wang, PengFei; Huang, GuoYou; Wang, Lin; Zhou, JinXiong; Lu, Tian Jian; Xu, Feng; Lin, Min
Abstract : A chemomechanical theory is proposed to describe the dynamic behavior and response time of ionic gels. Abstract : A chemomechanical theory is proposed to describe the dynamic behavior and response time of ionic gels. The large deformation of these gels accompanied by the migration of mobile ions is driven by a common non-equilibrium chemical reaction. The theoretical model was validated using existing experimental data. Further investigations showed that the dynamic deformation and response time of an ionic gel are dependent on the concentration of reactive and non-reactive ions, the time of exposure to external stimuli, the initial state and the density of ionizable groups on the polymer chains.